Ease and Difficulty in L2 Pronunciation Teaching: A Mini-Review - O’Brien, Mary Grantham (Frontiers in Communication, 2021)
Both L2 learners and their teachers are concerned about pronunciation. While an unspoken classroom goal is often accent-free speech, pronunciation researchers tend to agree that comprehensible speech (i.e., speech that can be easily understood by an interlocutor) is a more realistic goal. A host of studies have demonstrated that certain types of training can result in more comprehensible L2 speech. When discussing issues related to teaching L2 pronunciation, we must consider the importance of setting priorities and of delivering effective pronunciation training that positively affects learners’ comprehensibility. This contribution considers research on training the perception and production of both segmental (i.e., speech sounds) and suprasegmental features (i.e., stress, rhythm, tone, intonation). Its focus on ease and difficulty has less to do with given pronunciation features than on: a) setting classroom priorities that place an understanding of L2 speech at the forefront; and b) delivering effective L2 pronunciation training. The goal of the mini-review is to help contextualize the papers presented in this collection.